2011
DOI: 10.2174/1874912701104010033
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Various Anthropometric Indices in Prediction of Cardiovascular Risk Among Adult Jains

Abstract: The present study was conducted on Jain population residing in Delhi to elucidate the effectiveness of various anthropometric indices as cardiovascular risk. A cross sectional sample of 48 adult Jain females (mean age=50.5yr) and 62 adult males (mean age=47.4yr) was studied. Various anthropometric and physiological measurements were taken on each subject. In the present study BMI was found to be a greater risk factor for cardiovascular health among Jain females supported by strong correlation of BMI with blood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
0
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 39 publications
0
0
0
Order By: Relevance
“…In the present study also, BMI was found to impose a greatest risk factor for high Blood pressure among Jain adults. Our finding are in congruence with studies conducted among Jain adults of Delhi (Dhall et al, 2011), Noor et al (2023), Asemu et al (2021), Singh et al (2017) and Panda et al (2017).…”
Section: Doi: 1034256/ijk2325supporting
confidence: 92%
See 3 more Smart Citations
“…In the present study also, BMI was found to impose a greatest risk factor for high Blood pressure among Jain adults. Our finding are in congruence with studies conducted among Jain adults of Delhi (Dhall et al, 2011), Noor et al (2023), Asemu et al (2021), Singh et al (2017) and Panda et al (2017).…”
Section: Doi: 1034256/ijk2325supporting
confidence: 92%
“…In this study, the obese (general and abdominal) participants had higher prevalence of hypertension and it was found that anthropometric variables and indices were positively associated with systolic and diastolic blood pressure (p ≤ 0.01). Similar findings were presented by Thanglen & Maheo (2022), Panda et al (2017), Dhall et al (2011), andAgrawal et al (2008). This negative correlation of the education of participants, family income, and socioeconomic status of participants with systolic blood pressure was found to be consistent with finding of Wang et al (2006) and Dun et al (2021).…”
Section: Doi: 1034256/ijk2325supporting
confidence: 89%
See 2 more Smart Citations